Utilizations and policy formulations of home garden (pekarangan) as agritourism area in East Java, Indonesia - ATANG TRISNANTO; RINEKSO SOEKMADI; HADI SUSILO ARIFIN; BAMBANG PRAMUDYA (Society for Indonesian Biodiversity, 2023)
Abstract. Trisnanto A, Soekmadi R, Arifin HS, Pramudya B. 2023. Utilizations and policy formulations of home garden (pekarangan) as agritourism area in East Java. Biodiversitas 24: 1450-1459. This study aims to determine the factors that play a role in successfully using a home garden (pekarangan) as an agritourism area. This is important as material for formulating designs for home gardens for sustainable agritourism areas. This research was conducted in Banyuwangi District, East Java Province. The data and information to develop a home garden utilization system were collected through field observations and interviews with relevant parties. This study uses Interpretive Structural Modeling (ISM) analysis to identify the determinants and develop design formulations for utilizing pekarangan for agritourism areas. The key elements of a system are generated from the interpretation of ISM analysis data, which shows the levels of system structure. ISM analysis was determined through an approach with five criteria to examine the binding strength within and between groups/levels, the relative frequency of oscillations/shocks, context, coverage (containment), and functional relationship, respectively. The results showed that management institutions need to develop financing schemes with financing institutions, both banks and non-banks, based on financial technology (fintech). As practical implications, affordable financing for farmers/providers of tourism products, with their aggregator avalists, is needed to improve the financial capacity of community-based tourism. The manager of the pekarangan agritourism area is an aggregator of regional business processes by building inter-village networks and connectivity to major tourist destinations. Thus, home garden-based agritourism is expected to create new tourism area units networked with the main tourist destinations to form network tourism destinations.